Preparation and characterization of poly(ethyl hydrazide) grafted oil palm empty fruit bunch for removal of copper and nickel ions from aqueous solutions - Johari, Ili Syazana (2012)
Poly(ethyl hydrazide) grafted oil palm empty fruit bunch fiber (peh-g-opefb) has been successfully prepared by heating poly(methyl acrylate) grafted opefb (pma-gopefb) at 60oC for 4 hours in a solution of hydrazine hydrate (15% v/v) in ethyl alcohol. The chelating ability of peh-g-opefb was evaluated using Cu(II) and Ni(II) ions in aqueous solution. The concentration of metal was determined by inductively coupled plasma optical emission spectrometry (ICP-OES). pH study was carried out in the pH range from pH 1 to pH 6. The results shows that the adsorption of Cu(II) is optimized at pH 5 while Ni(II) is at pH 6. Isotherm study conducted for both metal ions reveals that the adsorption follows Langmuir isotherm model with maximum adsorption capacity of 43.48 mgg-1 at 25 ⁰C and 76.92 mgg-1 at 75 ⁰C for copper ion whereas for nickel ion, the maximum adsorption capacity is 42.19 mgg-1 at 25 ⁰C and 51.02 mgg-1 at 75 ⁰C. Kinetic study shows that the adsorption of copper and nickel ion follows pseudo-second-order kinetic model. Thermodynamic study was carried out in order to determine the thermodynamic parameters Gibbs free energy,ΔG⁰,entropy, ΔS⁰ and enthalpy value, ΔH⁰ of the adsorption process. The negative values of ΔG⁰ indicates that both copper and nickel adsorption onto poly(ethyl hydrazide) grafted opefb is a spontaneous process. Positive entropy, ΔS⁰ indicates that the system became more disorder during bioadsorption process whereas positive enthalpy, ΔH⁰ value shows that the adsorption of copper and nickel onto peh-g-opefb is an endothermic process. Selectivity study was done in mix solution of copper or nickel ions with various concentrations of interference ions including Na(I), Ca(II), Mg(II) and Cr(III). The results show that the adsorption of copper and nickel ions by peh-g-opefb was not affected by the presence of the interference ions even in high concentrations. Therefore, the peh-g-opefb is a potential and useful adsorbent which can be applied in many industries particularly related to toxic metal release.